ERRATA - F. R. FOSEERG (REINWARDTIA, 1965)
In the article entitled "Revision of Albizia Sect. Pachysperma (Leguminosae-mimosoideae)" by F. R. Fosberg, Reinwardtia 7: 71-90, 1965, the following changes should be made.